An introduction to ordinary differential equations - Agarwal, Ravi P. 1947-; O'Regan, Donal (Universitext, 2008)
This textbook provides a rigorous & lucid introduction to the theory of ordinary differential equations, which serve as mathematical models for many exciting real-world problems in science, engineering, and other disciplines.